Production Time Optimization By Six Sigma DMAIC Method At Goods Project Convection (The Indonesian Journal of Business Administration, 2021)
Goods Project is a company engaged in online-based convection in the city of Bandung, which was founded on February 1, 2016. In the last few years, the Goods Project has seen that the production process is still not optimal because it always experiences from a predetermined schedule when producing large quantities. This may occur because the production system is not optimal and there are small errors that are not noticed by management, causing these errors to always occur.Therefore, the author tries to do research related to the problems placed by the Goods Project using he Six Sigma concept with the DMAIC method (Define, Measure, Analyze, Improve, and Control). From the results of the root cause analysis it was found that the problem was in the Human, Method, Machine, and Measurement factors. In the method factor, it is found the order that the scheduling is irregular and also the information on the remaining invoice payments which results in the expenditure of raw materials. Factors It was found that employees do not have work contracts so that it causes no commitment with the company and understanding of the established SOPs, and also no KPI in employee performance appraisals. In the measurement factor, the company does not apply KPI to production capacity and time, which results in an ineffective production process. Furthermore, on the machine factor, the use of manual screen printing tools requires a longer time and also more labor, besides that there are still some sewing machines that do not operate due to lack of labor.Then the authors conducted a brainstorming related to the results of the analysis to optimize the production system. The upgrade phase (Upgrade) results in that the Goods Project can solve the problem by applying KPIs to several parts of the company especially on the administration, production & human resources systems and also implementing a more effective scheduling system. Then carry out control (Control) on the implementation of the strategy that has been done.Keywords: Six Sigma, DMAIC, Root Cause, Fishbone, KPI